Aetiologies of creeping eruption: 78 cases. (1st May 2014) - Vanhaecke, C.; Perignon, A.; Monsel, G.; Regnier, S.; Paris, L.; Caumes, E.
Summary: Background: Creeping eruption is a migratory linear cutaneous trail. In addition to hookworm‐related cutaneous larva migrans (HrCLM), other diseases can also be revealed by this sign. Objectives: To report the different aetiologies of creeping eruption. Methods: All consecutive patients with creeping eruption presenting to our unit in Pitié Salpêtrière Hospital in Paris between 1 March 2008 and 31 January 2013 were included. The diagnoses were based on microscopic data when available (hookworm folliculitis, strongyloidiasis) or the association of epidemiological, clinical, biological features and good outcome after specific treatment (HrCLM, loiasis, gnathostomiasis). Results: Seventy‐four patients (95%) presented with HrCLM. All but one had been travelling in a tropical country; seven (9%) also presented with folliculitis. Skin scraping of hookworm folliculitis lesions was performed in five cases and revealed living nematode larvae in three cases. Two patients (3%) with cutaneous gnathostomiasis after returning from Bali and Japan presented with intermittent creeping dermatitis on the foot and thigh, respectively. One patient (1%), native to Cameroon, was diagnosed with loiasis and one patient (1%), with no travel history, presented with 'creeping hair'. Conclusion: Hookworm‐related cutaneous larva migrans explains 95% of the cases of creeping eruption; gnathostomiasis, loiasis and cutaneous pili migrans may also be diagnosed.